Jiwa-Jiwa yang Terlupakan: Khotbah Feminis Pascakolonial tentang Peran Perempuan dalam Misi di dalam Narasi Kontemporer sebuah Gereja Lokal di Indonesia - Merlin Brenda Angeline Lumintang (STFT Jakarta, Indonesia, 2022)
The stories of the western male missionary are commonly and widely known in mission history. This article, however, reclaims the widely forgotten stories of women missionaries as authentic mission narratives relevant to the contemporary mission preaching conducted in the local Indonesian churches such as the Evangelical Christian Church in Minahasa. This article uses a feminist postcolonial perspective to argue that women missionaries are postcolonial subjects. It further uses their narratives to shape the local church's sermon as a